A cross-sectional study of the prevalence of metabolic syndrome and associated factors in colombian collegiate students: The fuprecol-adults study (2017)
Metabolic syndrome (MetS) is one of the major public health problems worldwide. The objective of the present study is to investigate the prevalence and the associated variables of MetS in Colombian collegiate students. This cross-sectional study included a total of 890 (52% women) healthy collegiate students (21.3 ± 3.2 years old). The prevalence of MetS was determined by the definition provided by the International Diabetes Federation (IDF). We further examined associations between the prevalence of MetS and related factors, such as age, gender, anthropometric and body composition, weight status, and nutrition profile. The overall prevalence of MetS was 6.0% (95% CI = 4.5% to 7.6%), and it was higher in men than women. The most prevalent components were low high-density lipoprotein cholesterol, high triglyceride levels, waist circumference, and blood pressure levels. The predisposing factors for having a MetS included: being male, over 23 years old, overweight or obese, and having an unhealthy waist-to-height ratio. In conclusion, the occurrence of MetS in young adults is substantial. These findings may be relevant to health promotion efforts for collegiate students in order to develop prospective studies and screening for young adults, which will aid in targeted intervention development to decrease cardiometabolic risk factors. © 2017 by the authors. Licensee MDPI, Basel, Switzerland.